Bridging the gap: simulation-based training in Nigeria (2015-2025) - Raphael Folorunsho Oluwasina Babatola; Evelyn Funke Folorunsho (International Journal of Public Health Science (IJPHS), 2026)
Medical education in Nigeria is transitioning from traditional apprenticeship-based training toward competency-based approaches. Simulation-Based Training (SBT) is increasingly recognized as a critical strategy for enhancing clinical competence and patient safety; however, its adoption across Nigeria remains fragmented and under-documented. This review aimed to map the extent, effectiveness, barriers, and future directions of Simulation-Based Training in Nigeria between 2015 and 2025. A PRISMA-ScR-guided systematic scoping review was conducted using peer-reviewed literature published between 2015 and 2025. Fifty-four eligible studies examining the implementation of SBT, outcomes, and contextual challenges across undergraduate and postgraduate health professional education in Nigeria were included. Data were synthesized narratively. Evidence indicates that SBT significantly improves technical skills, clinical decision-making, and learner confidence, particularly in high-risk areas such as neonatal resuscitation, surgical skills training, and obstetric emergencies. Institutional capacity has expanded through early adopters, including the University of Ilorin, the University of Lagos, and the University of Port Harcourt, and was reinforced by a 2025 federal initiative to establish eight national simulation centers. However, key barriers persist, such as high procurement costs (55%), unstable power supply (32%), and a shortage of trained simulation faculty (33%). Innovative low-cost approaches, including mobile virtual reality (mVR) and AI-enabled simulation platforms, emerged as promising alternatives to traditional infrastructure-heavy models. Simulation-based training demonstrates substantial educational value in Nigeria, but remains constrained by financial, infrastructural, and human resource limitations. National policy integration, mandatory simulation hours within MBBS and nursing curricula, and a structured “Training-the-Trainer” program leveraging digital and mobile simulation technologies are essential to achieving sustainable scale-up and improving patient safety outcomes in Nigeria and the wider West African region.